In vitro Interactions of Chicken Programmed Cell Death 1 (PD-1) and PD-1 Ligand-1 (PD-L1) - Reddy, Vishwanatha R. A. P.; Mwangi, William; Sadigh, Yashar; Nair, Venugopal (Frontiers in Cellular and Infection Microbiology, 2019)
In the present study, we determined the in vitro characteristics and binding interactions of chicken PD-1 (chPD-1) and PD-L1 (chPD-L1) and developed a panel of specific monoclonal antibodies against the two proteins. ChPD-1 and chPD-L1 sequence identities and similarities were lower compared with those of humans and other mammalian species. Furthermore, in phylogenetic analysis, chPD-1 and chPD-L1 were grouped separately from the mammalian PD-1 and PD-L1 sequences. As in other species, chPD-1 and chPD-L1 sequences showed signal peptide, extracellular domain, a transmembrane domain and intracellular domain. Based on the three dimensional (3D) structural homology, chPD-1, and chPD-L1 were similar to 3D structures of mammalian PD-1 and PD-L1. Further, Ig V domain of chPD-1 and the Ig V and Ig C domains of chPD-L1 were highly conserved with the mammalian counterparts. In vitro binding interaction studies using Superparamagnetic Dynabeads® confirmed that recombinant soluble chPD-1/PD-L1 fusion proteins and surface chPD-1/PD-L1 proteins interacted with each other on COS cells. Two monoclonal antibodies specific against chPD-1 and five antibodies against chPD-L1 were developed and their specific binding characteristics confirmed by immunofluorescence staining and Western blotting.